Healthcare and the Medical Architecture of Total Wellness - A. Goh, Nurakmal; S. Samat, Yon; K, Bambang; Utaberta, Nangkula (International Journal of Engineering and Technology, 2019)
The quest for knowledge of how our body works has become preoccupations habit to most people; with the development in digital technology, one could find numerous website that discuss about healthcare with a click away. Awareness of oneâ€™s personal health, prevention of illness has become a culture, especially for the people whom concerns on their health and beauty. Healthcare facilities too is moving towards a reform and people who go to the doctor do not necessary suffer from acute illness. These phenomenon is fast approach and it is crucial to review the approach in planning and design of healthcare facilities and the medical architecture; combining both art and science of medicine and architecture towards a total wellness of healthcare environment.Â Â